2000
DOI: 10.1104/pp.122.4.1335
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Allene Oxide Synthase Determines Defense Gene Activation in Tomato

Abstract: Allene oxide synthase (AOS; hydroperoxide dehydratase; EC 4.2.1.92) catalyzes the first step in the biosynthesis of jasmonic acid from lipoxygenase-derived hydroperoxides of free fatty acids. Using theAOS cDNA from tomato (Lycopersicon esculentum), in which the role of jasmonic acid in wound-induced defense gene activation has been best described, we examined the kinetics of AOS induction in response to wounding and elicitors, in parallel with that of the wound-inducible PIN II (proteinase inhibitor II) gene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(123 citation statements)
references
References 34 publications
3
114
0
4
Order By: Relevance
“…It has been suggested that AOS is a major control point in the octadecanoid signaling pathway (42,43). However, overexpression of the plastidic flax AOS cDNA in transgenic potato plants was not enough to trigger a constitutive expression of wound-or jasmonate-responsive genes, even though the plants contained 6-to 12-fold increased levels of JA (11).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that AOS is a major control point in the octadecanoid signaling pathway (42,43). However, overexpression of the plastidic flax AOS cDNA in transgenic potato plants was not enough to trigger a constitutive expression of wound-or jasmonate-responsive genes, even though the plants contained 6-to 12-fold increased levels of JA (11).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of several CYP74-enzymes has previously been described to be located in plastids [3]. Analysis of amino acid sequences of different cloned members of the CYP74 family revealed the presence of plastidic transit peptides [ 25,26,27]. The deduced amino acid sequence of AsDES lacks such a typical transit peptide.…”
Section: Isolation Of a Cyp74-enzyme From Garlicmentioning
confidence: 97%
“…Gene expression of lipoxygenases and cytochrome oxides (СYР74) is regulated by JA and its derivatives [4,8,62]. Enhancement of aoS genes transcription in cells and increase in AOC activity occur when leaves are wounded [63]. Promoters of many genes of the enzyme family cytochrome oxidases were revealed to have elements sensitive to stress signals by JA, SA and ethylene [63,64].…”
Section: Regulation Of Lipoxygenase Signaling System Activitymentioning
confidence: 99%